Factors that influence Malay teachers' attitude towards egalitarian education in multiracial society - Nek Rakami, Nik Muhammad Hanis; Ismail, Nik Ahmad Hisham (European Centre for Research Training and Development UK, 2019)
The purpose of this study is to explore potential relationship between Malay teachers’ characteristic factors and their attitudes towards egalitarian education in multiracial society. The ethnic Malay school teachers, teaching in government school in peninsular of Malaysia (N=400) participated in this study by completing a questionnaire, which developed by the authors. This questionnaire consists of five items concerning teachers’ characteristic (age, gender, teaching experience, school location and number of schools that teachers have being taught) and 20 Likert- based questions assessing teachers’ attitudes towards egalitarian education in multiracial society, which segmentized into four factors namely Malay Privileges in Education, Meritocracy, Monotype School System and Environmental Support for Underachievement. A multiple regression analysis was performed to explore relationship between Malay teachers’ characteristics and their attitudes towards egalitarian education in multiracial society. The findings indicated that there was statistically significant correlation between Malay teachers’ attitudes toward egalitarian education and their number of school that they have being taught. In contrast, there were no statistically significant correlation between teachers’ attitudes toward egalitarian with gender, age and teaching experience of Malay teachers. The findings concluded that Malay teachers with more number of schools that they have taught are more positive towards egalitarian education.